Evaluating the impact of virtual reality on student learning outcomes in higher education: A mixed-methods study from Zambia - John Pamba; Ng’andu Mwiya; Calvin Silwizya; Betty Shitima Bweupe; Simon Banda; Mushikwa Chanda; Natalia Zulu (Piramida Akademi, 2026)
Virtual and Augmented Reality (VR and AR) technologies are increasingly recognized as transformative tools in education, offering immersive learning experiences that enhance engagement and understanding. This study explored the impact of VR and AR on higher education at Zambia University College of Technology (ZUT), guided by Constructivist Learning Theory, which emphasizes active, experiential learning. An embedded mixed-methods design was used. Quantitative data were collected through surveys (N = 286), determined using the Yamane formula with a 5% margin of error and simple random sampling, while qualitative insights were obtained via semi-structured interviews and institutional document analysis. Selected students also engaged directly with Meta Quest VR headsets to assess usability and learning outcomes. Quantitative analysis using descriptive statistics, t-tests, and ANOVA showed that while awareness of immersive technologies is relatively high, implementation remains limited. VR-based instruction in graph theory led to significantly higher post-test scores (average = 78.7%) compared to traditional methods (average = 56.2%), reflecting enhanced engagement and conceptual understanding. Thematic analysis of qualitative data identified key barriers, including high infrastructural costs, limited technical expertise, and absence of formal institutional policies. These findings provide practical insights for strategic planning and evidence-based policy development to support the integration of immersive technologies in higher education in Zambia and the broader region.